2 Coronary flow reserve and index of microvascular resistance in acute stemi. (24th April 2016) - Carrick, David; Haig, Caroline; Ahmed, Nadeem; McEntegart, Margaret; Petrie, Mark C; Eteiba, Hany; Lindsay, Mitchell; Hood, Stuart; Watkins, Stuart; Davie, Andrew; Mahrous, Ahmed; Rauhalammi, Sam; et al.
Abstract : Background: Despite the success of emergency PCI for acute STEMI, failed myocardial reperfusion (microvascular obstruction) is common and prognostically important, but it commonly passes undetected in clinical practice. Purpose: To investigate coronary flow reserve (CFR) and the index of microvascular resistance (IMR) in the culprit coronary artery in patients with acute reperfused STEMI. Methods: CFR and IMR were measured at the end of PCI using guidewire-based thermodilution (n = 283; mean age 60 (12) years, 73% male). CMR imaging was used to assess left ventricular (LV) function and infarct pathology 2 days and 6 months post-MI (n = 264). All-cause death or first heart failure hospitalisation (ACD) was a pre-specified outcome that was assessed during follow-up (median duration 845 days). Results: The median [IQR] CFR was 1.6 [1.1–2.1] and the median IMR was 25 [15–48]. Microcirculatory status was associated with Killip Heart Failure classification, ST-segment resolution, LV ejection fraction and infarct size and pathology revealed by CMR 2 days later. In multivariate analysis, the combination of a CFR <2.0 and an IMR >25 was associated with changes in both LV ejection fraction (-2.47 (95% CI: -4.45, -0.49); p = 0.015) and LV end-diastolic volume (8.49 (1.96, 15.92); p = 0.025), and a CFR < median and an IMR > median was a multivariable (2.96 (1.24, 7.08); p = 0.015) associate of ACD. Conclusions: The combination of a reduced CFR and an increased IMR immediately identifies patients who have a substantially increased risk of adverse LV outcomes and all-cause death or heart failure.